Does tax amnesty influence intention to comply?: If students are taxpayers already - Damayanti, Theresia Woro; Nastiti, Pambayun Kinasih Yekti; Supramono, Supramono (Business, Management and Economics Engineering, 2020)
Purpose – The implementation of the tax amnesty program in Indonesia is expected to increase the intention to comply. However, the effectiveness of the program is likely to depend on the intention of taxpayer compliance. The purpose of this study is to examine differences in the intention of taxpayer compliance based on perceived justice and the taxpayer’s attitude of the government. Research methodology – Primary data was obtained through experimental research involving 117 students who were enrolled in the taxation class. To ensure that participants understand their role as taxpayers in an experiment, a role test is performed and this also acts as a test of internal validity. Findings – The results showed that there was a difference in the intention to comply based on perceived justice over the implementation of tax amnesty and taxpayers’ attitudes of government. Further analysis indicated that if taxpayers feel justice and have a positive attitude towards the government, it will lead to the highest intention to comply. Research limitations – The relationship between the justice variable on tax amnesty and the intention to comply is also possibly influenced by the existence of other variables such as feelings of disappointment. Therefore, in the future, it is necessary to do a study involving feelings of distress as a moderating variable in the relationship between justice and tax amnesty to comply. Practical implications – The government should continue to improve the performance and taxation system in order to create a positive attitude among taxpayers so that they will eventually comply with their tax obligations. Originality/Value – There are no previous studies that examined the interaction effect between the perceived justice of tax amnesty and taxpayer’s attitudes towards the government on intentions to comply.